Sustainable Innovation: Pushing the Boundaries of Traditional Operations Management. Issue 12 (28th October 2019) - Van Wassenhove, Luk N.
Abstract : The UN Sustainable Development Goals are not optional. They are about survival. Reaching them requires focus and strong innovation. Operations Management is about designing innovative business models to allocate scarce resources. It therefore has the toolkit to help move the sustainability agenda, provided it strongly opts for studying relevant and pressing problems and proves its potential impact. This study argues that this requires innovation as well as a paradigm shift in how we look at contributions. The good news is that a growing number of OM academics select to work on important facets of sustainability. The bad news is that we stepped into this field relatively late so the impact of that work is still modest. We need to push the boundaries of our discipline to develop new context‐dependent knowledge on pressing problems, provide evidence of the validity of our findings, and translate them into practical and easy‐to‐use decision tools. This study uses closed‐loop supply chains and humanitarian operations to illustrate and support this thesis. OM needs innovation to substantially contribute to the sustainable development agenda and thereby safeguard its own sustainability as a discipline.